2013
DOI: 10.1002/chem.201303329
|View full text |Cite
|
Sign up to set email alerts
|

How Can a Carbene be Active in an Ionic Liquid?

Abstract: The solvation of the carbene 1-ethyl-3-methylimidazole-2-ylidene in the ionic liquid 1-ethyl-3-methylimidazolium acetate was investigated by ab initio molecular dynamics simulations in order to reveal the interaction between these two highly important classes of materials: N-heterocyclic carbenes with superb catalytic activity and ionic liquids with advantageous properties as solvents and reaction media. In contrast to previously published data on analogous systems, no hydrogen bond is observed between the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 85 publications
4
40
0
Order By: Relevance
“…, which is quite close to the one already calculated with similar schemes (85 kJ mol À1 [22] ) by using localized basis sets. However, early studies based on the restricted Hartree-Fock scheme on the same NHC reported a smaller dissociation energy of about 66 kJ mol À1 .…”
supporting
confidence: 81%
“…, which is quite close to the one already calculated with similar schemes (85 kJ mol À1 [22] ) by using localized basis sets. However, early studies based on the restricted Hartree-Fock scheme on the same NHC reported a smaller dissociation energy of about 66 kJ mol À1 .…”
supporting
confidence: 81%
“…24,25 Very recently, new insights in the understanding of solute-solvent interactions within IL were provided from a theoretical study on the solvation of a carbene 1-ethyl-3-methylimidazole-2-ylidene in 1-ethyl-3-methylimidazolium acetate. 26 It was shown that the lack of strong hydrogen bonding between the hypovalent carbon atom of the carbene and the ring hydrogen atoms of the cation prevents the stabilization of this species explaining its high reactivity in acetate-based ILs. Overall, these studies converge towards a common recognition about the existing synergy between the cation and anion of the IL in the chemisorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[3] For instance, imidazolium-based ILs can be converted into their corresponding 1,3-dialkylimidazole-2-ylidene, an N-heterocyclic carbene (NHC), by a single deprotonation. [4] NHCs derived from thiazolium, imidazolium, and triazolium salts have emerged as an established catalytic method for making CÀC bonds in the field of organocatalysis. [5] Although being a facile and inexpensive way of generating NHCs, the connection between ILs and CÀC bond-forming NHC catalysis is rather poorly exploited.…”
mentioning
confidence: 99%